Pengaruh Kepemimipinan terhadap Turnover Intention Pada PT Massindo Karya Prima Pekanbaru - Srimulatsih, Mahbubah (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
This research was conducted at PT. Massindo Karya Prima Pekanbaru. This researched analysed the effect of leadership on turnover intention. It has 34 samples and using the method of quota sampling where all the samples were the employees. This research used quantitative method in order to analysed the data. We found that the leadership has the effect on turnover intention at PT.Massindo Karya Prima Pekanbaru. the linear regression result was Y= 28.010 – 0.038x. The t-test showed bigger than t-table where t-test was -3.218 > t –table 1.694 and significant because the significant level was 0.003 < 0.05 .